Street Vendor Strategies for Increasing Income from a Sharia Economic Law Perspective - Wahyudi, Muh. Hikmah; Jafar, Ahmad Ridha (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The problem studied in the thesis concerns sales strategies for street vendors. The research aims to find out the buying and selling procedures for street vendors in carrying out their strategies to increase income under Sharia economic law. In answering this problem, the author uses a sharia economic and sociological approach, while the type of research used is qualitative. With data collection procedures through field research, the author's data collection technique is to conduct observation, interviews, and documentation. In terms of data management and analysis techniques used by the author, namely inductive and deductive methods. The results of the research show that the strategy of street vendors to increase income from a sharia economic law perspective is analyzed from the traders' income as well as in terms of their strategy. Marketing is based on maintaining product quality, setting prices, carrying out promotions, strategic locations, and providing good service. From the perspective of Sharia economic law, seen from street vendors in Atapange Hamlet, some traders commit fraud by reselling the rest of their merchandise, but some act honestly according to Islamic law in terms of the quality of their merchandise.